The Influence of Self-Efficacy and Workload on Employee Performance Through Organizational Citizenship Behavior at Widya Kartika University Surabaya - Annisa Fajar Kinanthi; Marsudi Lestariningsih (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study aims to analyze the relationship between self-efficacy and workload on employee performance with Organizational Citizenship Behavior (OCB) as a mediating variable at Widya Kartika University Surabaya. This research adopts a quantitative approach using a survey method. The population of this study consists of all employees of Widya Kartika University Surabaya, with a total sample of 42 respondents selected using a saturated sampling technique. Data were collected through questionnaires using a five-point Likert scale and analyzed using path analysis. The results show that self-efficacy does not have a significant relationship with employee performance (p = 0.613). Meanwhile, workload has a positive and significant relationship with employee performance (p = 0.001). Organizational Citizenship Behavior (OCB) also has a positive and significant relationship with employee performance (p = 0.009). The mediation analysis indicates that Organizational Citizenship Behavior (OCB) is able to mediate the relationship between self-efficacy and employee performance (p = 0.030), but it is not able to mediate the relationship between workload and employee performance (p = 0.107). These findings suggest that OCB plays an important role in strengthening the effect of self-efficacy on employee performance, although it does not mediate the effect of workload.